Literature Review: HPV Vaccine Development Over Time - Kumara, Thoma (Jurnal KESANS : Kesehatan dan Sains, 2025)
Cervical cancer is the fourth most common cancer case in the world. The mortality rate caused by this disease also high especially in the low and middle income countries including Indonesia. In an attempt to decrease the mortality rate, WHO and the government work on strategies, one of which is HPV vaccination by adding HPV vaccine into routine immunization program given to girls on primary school. This study aims to review and analyze literatures about HPV vaccine. The result shows that HPV vaccine has a significant efficacy on preventing cervical cancer, even more effective once given as early as possible towards adolescents. The vaccine’s dose required in order to form a long term protection is still being studied but some researchs find that a single dose is on par with 2 or even 3 doses in terms of giving protection. Further and longer duration of research needed in order to support this theory. That way, the limited amount of vaccine could be directed to a larger population and in the end formed the long awaited herd immunity.